Determining the Reliability of Software Electronic Engineering Tools in the Control of Vestibular Disorders in Inclusive Physical Education of Students - Oksana Blavt; Gennadii Iedynak; Lesia Galamanzhuk; Tetiana Helzhynska; Yuliya Nosko; Yurii Kachurak; Olena Voloshyn; Stepan Shabaga (OVS LLC, 2024)
Background. Due to the increase in the proportion of mine-blast injuries sustained during the Russian-Ukrainian war, the number of students in higher education institutions after blast TBI has risen. Objectives. The study aimed to determine the reliability of the tool for test control of gait parameters, created based on software electronic engineering for students after blast TBI in inclusive physical education. Materials and methods. The theoretical stage of the research was realized by analyzing the literature on the studied problem, evaluating and synthesizing information from scientific sources. For the empirical part of the experiment, the Dynamic Gait Index test was used to assess gait parameters, dynamic balance, and fall risk. The test results were processed using the methods of statistical mathematical analysis. The experiment involved 30 students (men) after sustaining an explosive traumatic brain injury. Results. The study presents the developed tool for testing gait parameters using the Dynamic Gait Index, which is based on the integration of various types of software electronic engineering services. The development uses motion, speed, pressure, and touch sensors. The information about the test exercise, recorded by the sensors, is sequentially transmitted by wireless communication means to the controller (Arduino Leonardo based on the ATmega32u4 microcontroller platform) and then to a PC, where the results are displayed on the monitor in digital and graphical form. The development uses a neural network and the Microsoft OneDrive cloud service to process information, which provides processing and storage of large amounts of test control data. The results of the empirical establishment of the Dynamic Gait Index quality measure, the characteristics of reliability and validity that were recorded by the teacher, are significantly inferior in numerical values to the correlation coefficient obtained by the results of the Dynamic Gait Index when the outcomes were recorded using the developed tool. Conclusions. The introduction of modern software engineering services into inclusive physical education of students represents a significant step forward in implementing an impartial control mechanisms for restoring damaged gait and balance functions, which have been recognized as a leading factor in disability caused by blast TBI, and contributes to ensuring the effectiveness of this process.